The effect of a topical combined anti-inflammatory antibiotic preparation on the outcome of third molar surgery - Butow, Kurt-Wilhelm (University of Pretoria, 2013)
Dissertation (MChD (Chir Max-Fac Med))--University of Pretoria, 2007.